Going Concern Opinion: A Signaling Theory Perspective - Nyimas alya tiara putri; Khairudin (International Journal of Economics, Business Management and Accounting (IJEBMA), 2026)
This study examines the factors influencing the issuance of going-concern audit opinions in companies listed on the Indonesia Stock Exchange. The phenomenon of a number of companies being delisted from the Indonesia Stock Exchange indicates problems related to the business continuity of public companies. This condition emphasizes the importance of the going-concern opinion as an early signal for investors and stakeholders regarding the company's ability to maintain its operational continuity. Therefore, this study aims to analyze the influence of audit quality, debt ratio, company size, and financial distress on going-concern opinions. The novelty of this study lies in testing the determinants of going-concern opinions using a sample of cross-sector companies on the IDX with the most recent observation period. This study uses a quantitative method with secondary data in the form of financial statements and independent auditor reports for the period 2021–2024. Data analysis was performed using logistic regression. The results show that audit quality, debt ratio , and financial distress have a positive and significant effect on going-concern opinions , while company size has no significant effect. Simultaneously, all independent variables have a significant effect on going-concern opinions